SP70 is a novel biomarker of hepatocellular carcinoma - Wang, Lin; Shi, Hui; Wei, Jia; Chen, Wen-Xiu; Jin, Yue-Xinzi; Gu, Chun-Rong; Mu, Yuan; Xu, Jian; Pan, Shi-Yang (Frontiers in Oncology, 2023)
Background: Tumor-specific protein 70 (SP70) was identified as a new biomarker associated with the proliferation and invasion of cancer cells. This study aimed to investigate the expression of SP70 in hepatocellular carcinoma (HCC) and assess its clinical value in the diagnosis and prediction of early HCC recurrence. Methods: A total of 1049 subjects from the First Affiliated Hospital of Nanjing Medical University were recruited in this study. Serum SP70, alpha-fetoprotein (AFP) and prothrombin induced by vitamin K absence II (PIVKA-Ⅱ) were measured. The diagnostic performance for HCC was obtained using the receiver operating characteristic (ROC) curve, and recurrence-free survival (RFS) was calculated using the Kaplan–Meier method. Univariate and multivariate analyses were performed to identify predictive factors of RFS. Results: SP70 was highly expressed in HCC cells and HCC tissue. Serum SP70 levels in the HCC group were significantly higher than in the benign liver diseases group and healthy control group (P<0.001). SP70 combined with AFP showed the best diagnostic performance (AUC=0.918, 95%CI [confidence interval]=0.901–0.935). Kaplan–Meier analysis revealed that patients with high SP70 levels had shorter median RFS than those with low SP70 levels (P=0.003). In addition, high SP70 levels were significantly associated with shorter RFS (P=0.037) in the AFP-negative subgroup. Univariate and multivariate analyses confirmed that preoperative serum SP70 level, tumor diameter and microvascular invasion were independent prognostic factors of RFS. Conclusion: SP70 is a promising biomarker in diagnosing HCC. High preoperative serum SP70 level is associated with an increased risk of early relapse and could be used as a valuable marker to predict early recurrence of HCC after resection.